Electrocatalysis of Oxygen Reduction Reaction on Shape-Controlled Pt and Pd Nanoparticles—Importance of Surface Cleanliness and Reconstruction - Devivaraprasad, Ruttala; Nalajala, Naresh; Bera, Bapi; Neergat, Manoj (Frontiers in Chemistry, 2019)
Shape-controlled precious metal nanoparticles have attracted significant research interest in the recent past due to their fundamental and scientific importance. Because of their crystallographic-orientation-dependent properties, these metal nanoparticles have tremendous implications in electrocatalysis. This review aims to discuss the strategies for synthesis of shape-controlled platinum (Pt) and palladium (Pd) nanoparticles and procedures for the surfactant removal, without compromising their surface structural integrity. In particular, the electrocatalysis of oxygen reduction reaction (ORR) on shape-controlled nanoparticles (Pt and Pd) is discussed and the results are analyzed in the context of that reported with single crystal electrodes. Accepted theories on the stability of precious metal nanoparticle surfaces under electrochemical conditions are revisited. Dissolution, reconstruction, and comprehensive views on the factors that contribute to the loss of electrochemically active surface area (ESA) of nanoparticles leading to an inevitable decrease in ORR activity are presented. The contribution of adsorbed electrolyte anions, in-situ generated adsorbates and contaminants toward the ESA reduction are also discussed. Methods for the revival of activity of surfaces contaminated with adsorbed impurities without perturbing the surface structure and its implications to electrocatalysis are reviewed.